Editing domains of Trypanosoma brucei mitochondrial RNAs identified by secondary structure. - Piller, K J (1995)
The posttranscriptional insertion and deletion of U residues in trypanosome mitochondrial transcripts called RNA editing initiates at the 3' end of precisely defined editing domains that can be identified independently of the cognate guide RNA. The regions where editing initiates in Trypanosoma brucei cytochrome b and cytochrome oxidase subunit II preedited mRNAs are specifically cleaved by a trypanosome mitochondrial endonuclease that acts like mung bean nuclease and therefore is single strand specific. The regions where editing initiates in virtually all examined preedited mRNAs are predicted to form loop structures, suggesting that editing domains could generally be recognized as prominent single-stranded loops. In contrast to preedited mRNA, edited mRNA can be either resistant or sensitive to cleavage by trypanosome mitochondrial endonuclease, depending on the reaction conditions. This selectivity appears dependent on the availability of extract RNAs, and in model reactions, edited mRNA becomes resistant to cleavage upon base pairing with its guide RNA. Natural partially edited mRNAs are also specifically cleaved with a sensitivity like preedited and unlike edited mRNAs, consistent with their being intermediates in editing. These results suggest that in vivo, the structure of editing domains could initially be recognized by the mitochondrial endonuclease, which could target its associated RNA ligase and terminal U transferase to begin cycles of enzymatic editing modifications.